The internationalisation of R&D and the knowledge production function - María García-Vega; Patricia Hofmann; Richard Kneller (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper considers the effect of acquisition FDI on the knowledge production function. We distinguish between acquisitions by MNEs from technologically leading countries and those behind the technological frontier. We show that both acquire similarly R&D intensive domestic firms, but there are important differences post-acquisition. Acquisitions from technologically intensive countries reduce domestic R&D effort, in favour of an increase in foreign technology transfers, which suggests complementarities in the knowledge assets of the MNE and the target firm as a reason for FDI. In contrast, consistent with technology sourcing FDI, acquisitions from non-leading countries increase internal R&D efforts.
Keywords: F23; O33; D22; L20; 330; MNE; knowledge production function; acquisition FDI; knowledge complementarities; technology sourcing; Multinationales Unternehmen; Direktinvestition; Forschung; Übernahme; Technologietransfer; Wissen; Produktionsfunktion; Theorie